2018
DOI: 10.1088/1361-6528/aaafa7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of growth parameters on self-catalyzed ITO nanowires by high RF-power sputtering

Abstract: ITO nanowires have been successfully fabricated using a radio-frequency sputtering technique with a high RF-power of 250W. The fabrication of the ITO nanowires has been optimized through the study of oxygen flow rates, temperatures and RF-power. The difference in the morphology of the ITO nanowires prepared by using a new target and a used target has been first observed and the mechanism for the difference has been discussed in detail. A hollow structure and air voids within the nanowires are formed during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…When the oxygen was adequate (O 2 = 0.2 sccm), the ITO film would be obtained. In our previous report [19], we found that the growth of ITO nanostructures only happened when the sputtering power is larger than 200 W. In this work, the power was selected with 200 W and 250 W. Generally speaking, the growth rate of film is proportional to the sputtering power [20]. Under the power of 200 W, the molecules reunited together and attached the substrate.…”
Section: Different Morphologies Of Ito Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the oxygen was adequate (O 2 = 0.2 sccm), the ITO film would be obtained. In our previous report [19], we found that the growth of ITO nanostructures only happened when the sputtering power is larger than 200 W. In this work, the power was selected with 200 W and 250 W. Generally speaking, the growth rate of film is proportional to the sputtering power [20]. Under the power of 200 W, the molecules reunited together and attached the substrate.…”
Section: Different Morphologies Of Ito Materialsmentioning
confidence: 99%
“…In our previous work, ITO nanowires have been fabricated through self-catalytic vapor-liquid-solid (VLS) mechanism by sputtering, which showed good conductivity and good transmittance [19]. In this paper, ITO materials with different morphologies have been fabricated by adjusting the oxygen flow rate and RF-power.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. We have fabricated ITO materials with different morphologies (film, nanoparticles, nanorods, and nanowires) by sputtering [ 18 ]; the RS of the sensor with appropriate ITO nanowires was 235.6 at the ethanol gas concentration of 400 ppm, and the response and recovery times are 10 s and 12 s [ 19 ]. Meanwhile, the excellent corrosion resistance gives tin oxide and its compounds a significant advantage in the detection of corrosive gas [ 20 ].…”
Section: Introductionmentioning
confidence: 99%